Excess Total Mortality in Italy: An Update to February 2023 with Focus on Working Ages - Alicandro, Gianfranco; Gerli, Alberto Giovanni; Centanni, Stefano; Remuzzi, Giuseppe; La Vecchia, Carlo (La Medicina del Lavoro, 2023)
Background: Italy had a persistent excess of total mortality up to July 2022. This study provides updated estimates of excess mortality in Italy until February 2023. Methods: Mortality and population data from 2011 to 2019 were used to estimate the number of expected deaths during the pandemic. Expected deaths were obtained using over-dispersed Poisson regression models, fitted separately for men and women, including calendar year, age group, and a smoothed function of the day of the year as predictors. The excess deaths were then obtained by calculating the difference between observed and expected deaths and were computed at all ages and working ages (25-64 years). Results: We estimated 26,647 excess deaths for all ages and 1248 for working ages from August to December 2022, resulting in a percent excess mortality of 10.2% and 4.7%, respectively. No excess mortality was detected in January and February 2023. Conclusions: Our study indicates substantial excess mortality beyond those directly attributed to COVID-19 during the BA.4 and BA.5 Omicron wave in the latter half of 2022. This excess could be attributed to additional factors, such as the heatwave during the summer of 2022 and the early onset of the influenza season.